Maternal Obesity Modifies the Impact of Active SARS-CoV-2 Infection on Placental Pathology - Francisca Carmo; Carla Ramalho; Susana Guimarães; Fátima Martel (Viruses)
Background: Obesity during pregnancy is associated with an elevated risk of severe COVID-19, including higher rates of maternal complications, intensive care admission, and adverse neonatal outcomes. The impact of combination of SARS-CoV-2 infection and maternal obesity in placental pathology has not been properly investigated. Aim: To compare the histopathological changes in the placenta induced by active SARS-CoV-2 infection in obese and non-obese patients. Methods: This retrospective cohort study included human placentas from non-obese women and pre-gestationally obese women with active SARS-CoV-2 infection (SARS and OB+SARS, respectively), and placentas from non-obese women and pre-gestationally obese women without SARS-CoV-2 infection (control and OB, collected in the post- and pre-pandemic periods, respectively). Results: A higher (50%) occurrence of ischemic injury and subchorionic fibrin deposits and a 15× higher risk of occurrence of these lesions were found in the OB+SARS group, in relation to control. In contrast, a 10% lower risk of developing chorangiosis in the OB+SARS group than the OB group was observed. Conclusions: An increased risk of lesions related to both maternal and fetal malperfusion and ischemic injury and a lower risk for chorangiosis exist in placentas from obese women affected by SARS-CoV-2 infection. Importantly, these differences were not observed in placentas from non-obese women.